Integrating Smart Drilling Technologies with Real-Time Logging Systems for Maximizing Horizontal Wellbore Placement Precision - Kayode Emmanuel Akinleye; Shereef Olayinka Jinadu; Chinelo Nwaamaka Onwusi; Agama Omachi; Onuh Matthew Ijiga (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The integration of smart drilling technologies with real-time logging systems has revolutionized horizontal wellbore placement by enhancing accuracy, operational efficiency, and decision-making capabilities. As the oil and gas industry explores increasingly complex and unconventional reservoirs, the demand for precise geosteering and real-time subsurface evaluation continues to grow. This paper examines the evolution of smart drilling tools and logging-while-drilling (LWD) systems, emphasizing their combined role in optimizing drilling trajectories. It presents a structured framework for system integration, focusing on bottom hole assemblies equipped with intelligent sensors, real-time data acquisition platforms, and drilling optimization algorithms. Through selected offshore and onshore case studies, the paper highlights practical applications and industry experiences, revealing both the benefits and limitations of current integration models. Challenges such as data latency, environmental constraints, and technical compatibility are critically analyzed. Furthermore, the study explores recent technological advancements, including the use of artificial intelligence, machine learning, and enhanced downhole communication tools. Finally, the research outlines strategic recommendations for industry stakeholders to promote efficient adoption and innovation in smart drilling practices. The findings demonstrate that fully integrated real-time systems not only improve well placement accuracy but also offer long-term value through reduced costs, improved safety, and sustainable hydrocarbon extraction.